Structural and thermodynamic characteristics of the exosite binding pocket on the human BACE1: A molecular modeling approach - Gutierrez, Lucas Joel (2010)
We report a molecular modeling study aimed to locate and provide the full structural characteristics of the exosite binding site of the BACE1. A three-step procedure was followed. In the first stage, we performed blind docking studies on the whole target surface. In a second stage, the mode of binding was further refined by molecular dynamics (MD) simulation. Finally, binding free energy calculations, through the MM-PBSA protocol, were carried out to gain insight into the stability and thermodynamics of the inhibitor located at the selected binding pockets. Twelve binding pockets were identified on the surface of BACE1 by blind docking studies. The calculations of binding free energies for the 12 complexes show that van der Waals interactions dominate the mode of binding of these complexes. The best ranked complex shows that residues Glu255-Pro258, Phe261, Gly264-Ala272, Asp311-Ala313, Ser315, and Asp317-Tyr320 are located within ∼6 Å from the INH located at the exosite. The hydrogen bonds formed between the INH peptide, residues Tyr1, Tyr3, and Leu7 with the BACE1 residues Leu267, Cys269, Trp270, Asp311, and Asp 317 can strengthen the binding of the BACE1-INH complex.